Political and Economic Situation in the Republic of South Africa and its Influence on Immigration - Łodejska, Klaudia (Respectus Philologicus, 2021)
Migration processes have accompanied man since the dawn of time. In the case of migration currents to South Africa after World War II, there are several factors influencing the decisions to migrate. There were several waves of migration, depending on the changing in the second half of the Twentieth century South Africa’s economic and political situation. To properly present the issue of migration to South Africa, both from Poland and other countries of the world, it is first necessary to focus on the events that enabled the development of a policy of racial segregation. Then focus on economic development during this period that determined the successive waves of migrants. The last, crucial element is focusing on emigrants and the reasons for their emigration. In the case of the Polish diaspora in South Africa, many people decided to leave Poland due to the political system that was in the communist period; they wanted to give their children a better start in life or simply wanted to develop professionally, which was not possible at that time in the country. The aim of this article is to present the political, economic, demographic and social factors that influenced migration to South Africa.